Alcohol septal ablation in patients with severe septal hypertrophy. Issue 6 (30th August 2019) - Veselka, Josef; Jensen, Morten; Liebregts, Max; Cooper, Robert M; Januska, Jaroslav; Kashtanov, Maksim; Dabrowski, Maciej; Hansen, Peter Riis; Seggewiss, Hubert; Hansvenclova, Eva; Bundgaard, Henning; ten Berg, Jurrien; et al.
Abstract : Objective: The current guidelines suggest alcohol septal ablation (ASA) is less effective in hypertrophic obstructive cardiomyopathy (HOCM) patients with severe left ventricular hypertrophy, despite acknowledging that systematic data are lacking. Therefore, we analysed patients in the Euro-ASA registry to test this statement. Methods: We compared the short-term and long-term outcomes of patients with basal interventricular septum (IVS) thickness <30 mm Hg to those with ≥30 mm Hg treated using ASA in nine European centres. Results: A total of 1519 patients (57±14 years, 49% women) with symptomatic HOCM were treated, including 67 (4.4%) patients with IVS thickness ≥30 mm. The occurrence of short-term major adverse events were similar in both groups. The mean follow-up was 5.4±4.3 years and 5.1±4.1 years, and the all-cause mortality rate was 2.57 and 2.94 deaths per 100 person-years of follow-up in the IVS <30 mm group and the IVS ≥30 mm group (p=0.047), respectively. There were no differences in dyspnoea (New York Heart Association class III/IV 12% vs 16%), residual left ventricular outflow tract gradient (16±20 vs 16±16 mm Hg) and repeated septal reduction procedures (12% vs 18%) in the IVS <30 mm group and IVS ≥30 mm group, respectively (p=NS for all). Conclusions: The short-term results and the long-term relief of dyspnoea, residual left ventricular outflow obstruction and occurrence of repeated septal reduction procedures in patients with basal IVS ≥30 mm is similar to those with IVS <30mm. However, long-term all-cause and cardiac mortality rates are worse in the ≥30 mm group.